1996
DOI: 10.1111/j.1601-0825.1996.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative periodontal pathogens, antibody titres and avidities to them in a longitudinal study of patients with resistant periodontitis

Abstract: OBJECTIVE: To study changes in antibody titres and antibody avidities to putative periodontal pathogens in patients with resistant periodontitis and to compare these findings with the result of culture of these pathogens. SUBJECTS AND METHODS: Patients meeting strict clinical criteria in whom periodontal therapy had failed to prevent disease progression were studied microbiologically and immunologically over a 75‐week period. Particular reference was made to the isolation of Actinobocillus actinomycetemcomiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These findings were extended to potential success or failure of the antibodies to protect the host effectively. A range of studies have suggested that the immune response to oral pathogens does not mature effectively, as estimated via antibody avidity [41–46], and could contribute to lowered protective capacity. Furthermore, examination of the effector functions of antibodies to the oral pathogens has provided some challenge due to, for example, the gingipains from P. gingivalis effectively degrade antibodies and complement components in vitro [47–49], and the leucotoxin from A. actinomycetemcomitans killing neutrophils [50–52] in test for opsonizing potential.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were extended to potential success or failure of the antibodies to protect the host effectively. A range of studies have suggested that the immune response to oral pathogens does not mature effectively, as estimated via antibody avidity [41–46], and could contribute to lowered protective capacity. Furthermore, examination of the effector functions of antibodies to the oral pathogens has provided some challenge due to, for example, the gingipains from P. gingivalis effectively degrade antibodies and complement components in vitro [47–49], and the leucotoxin from A. actinomycetemcomitans killing neutrophils [50–52] in test for opsonizing potential.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, both the specificity and levels of serum antibody responses to oral pathogens are clearly related to periodontal disease (50,58,77,81,82). Both antibody frequency and level increase with increasing severity of periodontal disease, and various studies have demonstrated that these serum antibody levels will be elevated following mechanical therapy and will correlate with response to treatment (50,(83)(84)(85)(86). Moreover, changes in serum antibody to selected oral pathogens appear to occur following emergence of the microorganisms in oral biofilm samples and prior to the identification of progressing disease (50,87).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chen et al (1991) reported that generalized aggressive periodontitis patients had lower antibody avidity, which increased following non‐surgical therapy. A study by Holbrook et al (1996) noted low antibody avidity to P. gingivalis in chronic periodontitis, which did not change with therapy including a combination antibiotic regimen.…”
mentioning
confidence: 99%